(\unicode{8523}\) means Parallel: Multiplicative Linear Logic Proofs as Concurrent Functional Programs - Aschieri, Federico; Genco, Francesco A (arXiv.org, 2019)
Along the lines of the Abramsky ``Proofs-as-Processes'' program, we present an interpretation of multiplicative linear logic as typing system for concurrent functional programming. In particular, we study a linear multiple-conclusion natural deduction system and show it is isomorphic to a simple and natural extension of \(λ\)-calculus with parallelism and communication primitives, called \(λ_{\unicode{8523}}\). We shall prove that \(λ_{\unicode{8523}}\) satisfies all the desirable properties for a typed programming language: subject reduction, progress, strong normalization and confluence.